INTERNALISASI NILAI ADAB SISWA MENURUT AL-GHAZALI DALAM PEMBENTUKAN KARAKTER PESERTA DIDIK - Zulfa Istinwaro Holik; Yuliana; Bunga Dewi; Benny Prasetiya (Educational Research Center, 2026)
This study aims to examine the concept of internalizing moral values (adab) according to Al-Ghazali and to identify its implications for the character formation of students in the contemporary era. Background: of this research stems from the importance of adab as a foundational element of education according to Imam Al-Ghazali. In light of the rampant moral degradation observed in students during the modern era, Al-Ghazali's ideas are deemed relevant in reinforcing educational objectives that emphasize not only intellectual abilities but also character formation, spirituality, and noble personality. Method: This research employs a literature review method with content analysis of Al-Ghazali's primary works such as